Urgensi Penegakan Hukum Perlindungan Data Pribadi Terhadap Praktik Penahanan Ijazah Oleh Perusahaan: Studi Kasus di Surabaya - tarigan, ridwan (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
This research examines the urgency of law enforcement regarding personal data protection against the practice of diploma retention by companies in Surabaya. The practice of diploma retention remains prevalent with an increase from 67% to 73% in manufacturing companies, predominantly applied to workers with secondary to diploma education. This study aims to analyze diploma retention practices from the perspective of Law Number 27 of 2022 on Personal Data Protection and its implications for Indonesia's constitutional system. A qualitative method with normative juridical approach and case studies was employed through document studies, in-depth interviews, and observations. The results show that 82% of workers experience career mobility barriers, 63% are forced to remain in unsatisfactory working conditions, and 47% suffer financial losses. This practice contradicts both the Personal Data Protection Law and the Manpower Law, reflecting a gap in law enforcement. Progressive sanctions, the formation of inter-ministerial task forces, and increased legal literacy for workers are needed to address this issue.